# -7=-8g-1+4g+3

## Simple and best practice solution for -7=-8g-1+4g+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for -7=-8g-1+4g+3 equation:

Simplifying
-7 = -8g + -1 + 4g + 3
Reorder the terms:
-7 = -1 + 3 + -8g + 4g
Combine like terms: -1 + 3 = 2
-7 = 2 + -8g + 4g
Combine like terms: -8g + 4g = -4g
-7 = 2 + -4g
Solving
-7 = 2 + -4g
Solving for variable 'g'.
Move all terms containing g to the left, all other terms to the right.
Add '4g' to each side of the equation.
-7 + 4g = 2 + -4g + 4g
Combine like terms: -4g + 4g = 0
-7 + 4g = 2 + 0
-7 + 4g = 2
Add '7' to each side of the equation.
-7 + 7 + 4g = 2 + 7
Combine like terms: -7 + 7 = 0
0 + 4g = 2 + 7
4g = 2 + 7
Combine like terms: 2 + 7 = 9
4g = 9
Divide each side by '4'.
g = 2.25
Simplifying
g = 2.25